Parenting Styles and Their Impact on the Emotional Intelligence of Adolescents at SMKN 1 Padang - Fadhila fitri; Rinaldi (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
This study aims to evaluate the impact of parenting styles on the emotional intelligence of adolescents at SMKN 1 Padang. Emotional intelligence is the ability to recognize, understand, and manage one's own emotions and the emotions of others. Parenting styles play a fundamental role in the development of emotional intelligence in adolescents. The research method applied is quantitative with a survey approach. Data were collected from questionnaires distributed to 208 students at SMKN 1 Padang. Data analysis was performed using multiple linear regression to examine the impact of parenting styles on emotional intelligence. The analysis results obtained an F value of 92.616 with a probability (P) of 0.000 < 0.005. This means that the regression coefficients of the parenting style variables collectively influence emotional intelligence. This explains that Ha is accepted and H0 is rejected. Overall, parenting styles contribute 57% to the variance in emotional intelligence of adolescents at SMKN 1 Padang. The significance values for authoritarian, authoritative, and permissive parenting styles are 0.004 (<0.05), 0.000 (<0.05), and 0.000 (<0.05), respectively, indicating that these parenting styles have a significant impact on emotional intelligence. The study results show that authoritative parenting style has a positive effect on adolescents' emotional intelligence. Conversely, authoritarian and permissive parenting styles have a negative impact. The influence of authoritative parenting style on emotional intelligence is 52%, permissive parenting style is 3%, and authoritarian parenting style is 2%. This study contributes to understanding how different parenting styles affect adolescents' emotional intelligence. The findings can serve as a reference for parents, educators, and policymakers in developing effective parenting strategies to enhance emotional intelligence and reduce juvenile delinquency.